(untitled) (Journal of Buffalo Science, 2015)
This survey aimed to investigate the incidence rate of some reproductive problems especially retained placenta and metritis in cattle and buffalo cows to design appropriate manners for correction and treatment of such disorders of those two important animals in Iraq. A field survey was carried out on 257 cattle cows during 2011 and 290 during 2012 and 383 local water buffalo cows (Bubalus bubalis), during 2011 and 404 during 2012 in some villages around Baghdad (Al-Fudalia, 7 Nisan and Basmaia) where animals were reared. A complete data about case history, owner complains, clinical examinations for reproductive status, were documented by private clinics during 2011 - 2012. Results revealed that retained placenta percentage in cattle was 12.84, 12.41% during 2011, 2012 respectively, whereas it was 12.53, 12.62% during 2011, 2012 respectively in buffalo cows, in the case of uterine infections percentages, buffalo exhibited the highest percentages (40.46,37.87 %) during 2011, 2012 respectively in the comparison with cattle which showed 35.40, 35.17 % during 2011,2012 respectively. Highly significant differences (p â‰¤ 0.01) between species were observed yearly and during some months during the years of study. We concluded that management programs differences and environmental changes may lead to monthly and yearly differences in reproductive disorders capability.